ESTUDIO COMPARATIVO FINANCIERO DE LAS COOPERATIVAS DE AHORRO Y CRÉDITO DEL SEGMENTO 2 DE LA CIUDAD DE LOJA, PERIODO 2015-2017 - MORENO GORDILLO, ANDREA MARITZA (2019)
This thesis work was developed with the aim of making a financial comparison between the Savings and Credit Cooperatives of segment two, "Father Julián Lorente", "De la Pequeña Empresa de Loja" (CACPE), and "Educadores de Loja" (CACEL), of the Loja city, managing to determine the divergences and similarities between them. To meet the proposed objectives, different methods and techniques were proposed, based on scientific, deductive, inductive, analytical and technical methods such as direct observation and bibliographic collection. In this context, for the fulfillment of the first objective, the technique of literature collection was used to collect the necessary information from each of the savings and credit unions under study to carry out the characterization of them. Likewise, through the quantitative method the second objective was developed through the application of the vertical analysis that allowed to determine the composition and structure of the financial statements and to know the degree of incidence of each of the accounts, identifying that for the three Savings and Credit Cooperatives the most representative account in the Asset was a credit portfolio with 74.67% CACPE Loja); 75.28%(Padre Julián Lorente) and 69.82%(CACEL), because of the granting of credits by cooperatives to their partners,. Similarly, the horizontal analysis was carried out, where existing variations from year to year were established with their respective causes. In addition, the financial indicators were applied with this being known that financial institutions are mostly within the limits set by SEPS. In the same way, the proforma financial statements were carried out, using the historical method and the method of personal judgment, which shows the availability of cash and possible utility that savings and credit unions would obtain if manage both the financial resources and the human talent it maintains in a more effective and efficient way, so that in the 2019 projection year there is greater operational efficiency. Finally, the work determined as the main conclusion that the cooperative that is best found with regard to its economic structure is Cacpe Loja, despite being one of the youngest cooperatives among those considered to carry out this research, then there is Father Julián Lorente, who is the oldest on the market and for this reason is more recognized among the lojana community, this is due to the advertising that this cooperative makes to attract its partners; on the contrary it happens with the Cacel, which is disadvantaged with the other cooperatives despite providing the same products and services, it does not have an ATM which creates a disadvantage, and the most important thing is that this institution is exclusively for a certain group of people who are those who are engaged in teaching.